Barriers and Challenges of Acoustic Design in Flexible Learning Spaces for Schools in Chile - Ipinza-Olatte, C (Springer Science and Business Media Deutschland GmbH, 2023)
This chapter addresses the regulatory barriers and acoustic design challenges for skills development in the twenty-first century in the Global South, within new flexible learning spaces. Nowadays, the diversity of teaching methodologies and approaches has made the ambient sound more complex due to the noise caused by group learning activities. Therefore, the objective of this article was to make an international review of acoustic design regulations and recommendations for flexible learning spaces. Currently, the limited acoustic design criteria for these new spaces differ from one another, evidencing impressions when defining which parameters would be optimal to characterize their acoustics. Understanding the operationalization of architectural design and pedagogical use will be essential to provide adequate verbal communication using variable acoustics, which involves the use of acoustic control elements and devices to cover the current gaps in existing standards. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.